Adding New Skill in Backpack: Examining Teacher Candidates’ Experiences with AI-Supported Presentation Design - Güneş, Habibe; Yaşli, Serap (Kafkas Üniversitesi, 2026)
The quality of presentation materials within the teaching through presentation approach, which has been widely used in teaching for many years, has been significantly transformed by the rapid development of artificial intelligence technologies and their integration into education. AI-supported presentations, enriched in terms of content production and visual design, enable the creation of learning environments that are sensitive to individual differences. Therefore, developing the skills of future teachers to effectively use artificial intelligence for pedagogical purposes in educational material development processes and integrating it into educational processes is critically important for increasing classroom interaction and diversifying teaching methods. Therefore, this research examines the experiences of 22 teacher candidates in their third year of undergraduate studies in social studies teacher education at a state university in preparing effective presentations using AI-supported presentation tools through collaborative pair work, using a mixed methods research approach. Quantitative data were collected using the Artificial Intelligence Readiness Scale and a peer-reviewed presentation evaluation rubric. Qualitative data were collected using semi-structured interview questions to examine the prospective teachers' practical experiences. Quantitative data obtained from the study were analyzed using SPSS software, while qualitative data were analyzed using NVivo content analysis. The results showed that teacher candidates' readiness for artificial intelligence increased after the application. By learning to use AI-supported presentation tools, they experienced positive changes in their attitudes towards technology. Individuals who previously had limited technological knowledge discovered that they could prepare effective and engaging presentations. In conclusion, teacher candidates gained more experience in technology, pedagogy, and content knowledge after the application, and their awareness and motivation for designing effective teaching materials increased.
Keywords: Instructional Technologies; Öğretim Teknolojileri; Teacher Education and Professional Development of Educators; Öğretmen Eğitimi ve Eğitimcilerin Mesleki Gelişimi